A sensitive element comprising a composite functional material, a method of preparation and a low hysteresis ionic gel type pressure sensor

CN122878736APending Publication Date: 2026-10-09WUTONG SENSATION CONTROL (BEIJING) TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611400360.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种包括复合功能材料的敏感元件、制备方法和低滞后离子凝胶型压力传感器,旨在解决现有的离子型压力传感器存在的聚合物机械强度较低,在压力加载、卸载的过程中,柔软的聚合物链段容易延迟回弹;以及离子液体可能发生迁移、聚集,从而导致传感器出现明显滞后的问题

Benefits of technology

[0016]1. 在本发明公开的敏感元件中,将介孔二氧化硅引入离子凝胶体系中,可以形成具有刚性骨架的复合压力传感薄膜;其中,介孔二氧化硅的多孔结构可以固定离子液体,使其在体系中均匀分散,并形成稳定的离子电导通路,也可以提升聚合物的机械强度。在压力加载过程中,离子通路受力变化产生可测的电学信号,同时刚性骨架支撑聚合物链段,抑制链段过度滑移或局部流动,从而显著降低了加载-卸载过程中的滞后现象,并抑制信号基线漂移。由于离子液体通路得到稳定固定,即使在反复循环压力作用下,薄膜的电学响应仍保持连续性和重复性。因此,该敏感元件具备高灵敏、快速响应和稳定高等特性,解决了现有的离子型压力传感器存在的聚合物机械强度较低,在压力加载、卸载的过程中,柔软的聚合物链段容易延迟回弹;以及离子液体可能发生迁移、聚集,从而导致传感器出现明显滞后问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878736A_ABST
    Figure CN122878736A_ABST
Patent Text Reader

Abstract

The application discloses a sensitive element comprising a composite functional material, a preparation method and a low-hysteresis ionic gel type pressure sensor, and belongs to the technical field of pressure sensors. By introducing mesoporous silica into an ionic gel system, a composite pressure sensor film with a rigid skeleton is formed. The porous structure of the mesoporous silica can fix ionic liquids, make the ionic liquids uniformly dispersed in the system, and form stable ion conduction paths, so that the mechanical strength of the polymer is improved. When pressure is loaded, a measurable electrical signal is generated, and the rigid skeleton supports the polymer chain segments, inhibits excessive slippage or local flow of the chain segments, reduces the hysteresis phenomenon, and inhibits signal baseline drift. The problems of low mechanical strength of the polymer, easy delay of the soft polymer chain segments to rebound and the hysteresis of the existing ionic pressure sensor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pressure sensor technology, and in particular to a sensitive element comprising composite functional materials, a preparation method thereof, and a low-hysteresis ion gel type pressure sensor. Background Technology

[0002] Pressure sensors, as core components of flexible electronics and intelligent sensing systems, are widely used in wearable electronics, electronic skin, health monitoring, flexible robots, human-computer interaction, and intelligent prosthetics, enabling real-time sensing and data acquisition of external pressure, force, or strain. These applications place high demands on the sensor's sensitivity, response speed, and stability. Based on signal conversion mechanisms, pressure sensors can be categorized into resistive, capacitive, piezoelectric, inductive, and ionocapacitive types. Resistive pressure sensors detect pressure changes through changes in the resistance of a conductive network; capacitive pressure sensors generate electrical signals through changes in the distance between electrodes or the dielectric constant; piezoelectric and inductive sensors rely on the piezoelectric effect or changes in inductance to detect external forces. Ionocapacitive pressure sensors, on the other hand, utilize the ion double-layer structure formed by ionogels, which causes changes in interface capacitance under pressure, thus achieving signal output. Compared to other types, ionocapacitive sensors offer advantages such as high sensitivity and fast response speed, providing high-precision and real-time pressure monitoring capabilities in flexible electronic devices.

[0003] In existing ionic pressure sensors that use ionic liquids as the main composite material, when a polymer is added to an ionic liquid, the ionic liquid will embed between the polymer chain segments to play a plasticizing role, which improves the flexibility of the polymer, but reduces its mechanical strength. During pressure loading and unloading, the soft polymer chain segments are prone to delayed rebound. At the same time, the ionic liquid may migrate and aggregate, which will cause the sensor to have a significant hysteresis, affecting sensitivity and repeatability. Summary of the Invention

[0004] The main objective of this invention is to provide a sensitive element comprising composite functional materials, a preparation method, and a low-hysteresis ion gel pressure sensor. This invention aims to address the problems of existing ion-type pressure sensors, such as the low mechanical strength of the polymer, the tendency of soft polymer chains to rebound slowly during pressure loading and unloading, and the potential migration and aggregation of ionic liquids, which can lead to significant hysteresis in the sensor.

[0005] To achieve the above objectives, the present invention provides a sensing element comprising a composite functional material, the sensing element comprising a multi-component composite functional material system formed of mesoporous silica; the multi-component composite functional material system formed of mesoporous silica comprises a polymer and a room-temperature ionic liquid; The sensitive element includes a multi-dimensional interpenetrating channel structure and a rough surface structure.

[0006] Optionally, the polymer comprises at least one of PVDF, TPU, PVDF-HFP, PU, ​​and PAN; the room-temperature ionic liquid comprises at least one of [EMIM][TFSI], [EMIM][TFA], [R-Py][X], and [NR4][X].

[0007] To achieve the above objectives, the present invention also provides a method for preparing a sensitive element comprising a composite functional material, for preparing the sensitive element as described above, the method comprising: An ionic gel system was prepared by adding a room-temperature ionic liquid to a solution of a polymer. Mesoporous silica powder phase was added to the ion gel system to prepare a multi-component composite functional material system formed by mesoporous silica. Based on the sensitive element fabrication process, the multi-component composite functional material system formed from mesoporous silica is used to prepare the sensitive element.

[0008] Optionally, the method for preparing an ionogel system by adding a room-temperature ionic liquid to a solution of a polymer includes: The solid phase of the polymer is dissolved in a solvent and magnetically stirred until homogeneous to obtain a polymer-based solution. The room-temperature ionic liquid was added to the polymer-based solution and stirred until homogeneous to obtain the ionic gel system.

[0009] Optionally, the method of adding mesoporous silica powder phase to the ion gel system to prepare a multi-component composite functional material system formed of mesoporous silica includes: The mesoporous silica powder phase is added to the ion gel system and stirred until homogeneous under ultrasonic conditions to obtain the multi-component composite functional material system formed by mesoporous silica.

[0010] Optionally, when the sensing element is fabricated using a solution casting method, the method for fabricating the multi-component composite functional material system formed from mesoporous silica into the sensing element based on the sensing element fabrication process includes: The multi-component composite functional material system formed by mesoporous silica is poured into a mold, coated with a scraper to a uniform thickness, and then subjected to preliminary drying and heat curing to obtain the sensitive element.

[0011] Optionally, in the ionogel system, the mass ratio of the polymer, the room-temperature ionic liquid, and the solvent is 1:1:4 to 1:1.5:5.

[0012] Optionally, in the step of adding the mesoporous silica powder phase to the ionogel system, the amount of the mesoporous silica powder phase added is 1.6-3.5% of the mass of the ionogel system.

[0013] Optionally, in the steps of preliminary drying and heat curing, the temperature of preliminary drying is 30-50℃ and the time is 30-45 min; the temperature of heat curing is 75-90℃ and the time is 5.5-6.5 h.

[0014] To achieve the above objectives, the present invention also provides a low-hysteresis ion gel pressure sensor, the pressure sensor comprising the sensitive element as described above.

[0015] Compared with the prior art, the beneficial effects that the present invention can achieve are as follows.

[0016] 1. In the sensitive element disclosed in this invention, mesoporous silica is introduced into an ion gel system to form a composite pressure sensing film with a rigid framework. The porous structure of the mesoporous silica can immobilize the ionic liquid, allowing it to disperse uniformly within the system and forming a stable ionic conductivity pathway. It can also enhance the mechanical strength of the polymer. During pressure loading, changes in force on the ionic pathway generate a measurable electrical signal. Simultaneously, the rigid framework supports the polymer chains, suppressing excessive slippage or localized flow, thereby significantly reducing hysteresis during loading-unloading and suppressing signal baseline drift. Because the ionic liquid pathway is stably fixed, the electrical response of the film remains continuous and repeatable even under repeated cyclic pressure. Therefore, this sensitive element possesses high sensitivity, fast response, and high stability, solving the problems of low polymer mechanical strength in existing ion-type pressure sensors, where soft polymer chains tend to rebound slowly during pressure loading and unloading; and the potential migration and aggregation of ionic liquids, leading to significant hysteresis in the sensor.

[0017] 2. The sensitive element obtained by the preparation method provided by the present invention is applied to a pressure sensor. The ion transport response of the ion gel in the sensitive element is extremely fast, and the pores of the mesoporous silica can further shorten the ion transport path, so that the sensor has low hysteresis characteristics. At the same time, by limiting the proportion of each component in the system, the sensor has the characteristics of flexibility, stretchability, wide temperature adaptability, anti-interference and high stability. Attached Figure Description

[0018] Figure 1 This is a surface microstructure diagram of the thin film morphology of the sensing element in Example 1; Figure 2The pressure-capacitance curve is shown for the thin-film ion gel pressure sensor containing the sensitive element of Example 1. Figure 3 The pressure-capacitance curve is shown for the thin-film ion gel pressure sensor containing the sensitive element of Example 2. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the following substances can be prepared by known methods or commercially available; in the process of substance preparation, unless otherwise specified, the reaction involving crosslinking agents, functional additives, temperature, and other reaction conditions are all considered to be known technical implementations. If not explicitly given in the text, it does not mean that the substances of this application cannot be obtained.

[0020] To address the problems of low polymer mechanical strength in existing ion-type pressure sensors, which leads to delayed rebound of soft polymer chains during pressure loading and unloading, and the potential migration and aggregation of ionic liquids causing significant sensor hysteresis, this invention provides a sensing element comprising a composite functional material. This sensing element includes a multi-component composite functional material system formed from mesoporous silica; the multi-component composite functional material system formed from mesoporous silica includes a polymer and a room-temperature ionic liquid. The sensitive element includes a multi-dimensional interpenetrating channel structure and a surface roughening structure.

[0021] It should be understood that in the technical solution of the present invention, the sensitive element is the sensitive layer or ion gel layer in the sensor component; depending on its working mechanism, it may also be called a conductive active layer, dielectric layer, electrolyte layer, transducer layer or functional layer; in the structure of the sensor, it is usually named the sensitive layer.

[0022] It should be understood that the aforementioned mesoporous silica is a porous silica material with a regular or disordered mesoporous structure. Its pore size is usually 2-50 nm, and it has a high specific surface area and pore volume, which can provide adsorption, loading or confinement space for other functional components.

[0023] Optionally, based on the scheme disclosed in this invention, the type of mesoporous silica can be selected according to actual needs and with reference to the prior art. For example, MCM-41 type, SBA-15 type or KIT-6 type mesoporous silica can be selected. It should be noted that in the aforementioned multi-component composite functional material system formed by mesoporous silica, the mesoporous silica acts as a rigid nanoframework dispersed in a flexible polymer matrix. Its high-modulus crystal structure can form numerous physical cross-linking points in the soft matrix. These cross-linking points interact with the polymer chains through hydrogen bonds, π-π stacking, and van der Waals forces, which not only preserves the overall flexibility of the material but also significantly improves the elastic modulus and rebound rate. When pressure is applied, the polymer chain segments deform, and the mesoporous silica framework bears part of the stress and stores elastic energy. After the pressure is unloaded, the interaction between the mesoporous silica and the polymer chains promotes the rapid recovery of the chain segments to their original conformation, avoiding the delayed rebound caused by chain segment entanglement and viscous resistance in pure polymers, thus solving the problems of low polymer mechanical strength and delayed rebound.

[0024] Furthermore, the pores of mesoporous silica provide nanoscale confinement spaces for ionic liquids. When ionic liquids enter these pores, their molecular motion is spatially constrained by the pore walls, reducing the diffusion coefficient and macroscopically manifesting as weakened migration ability. Ionic liquids may be anchored within the mesoporous silica pores, making macroscopic migration and phase separation difficult even under long-term pressure cycling or temperature fluctuations. Moreover, the inner walls of the mesoporous silica pores typically contain abundant silanol groups and silicon-oxygen bonds, where the silanol groups can react with ionic liquid anions, such as [TFSI]. - The sulfonyl oxygen in the PVDF forms hydrogen bonds, and the oxygen atoms on the pore wall surface can also form hydrogen bonds or electrostatic interactions with the C-H groups on the cation ring, thereby enhancing the adsorption and interfacial confinement of ionic liquids by mesoporous silica, and confining the ionic liquid through the mesoporous channels. This strong interfacial interaction causes the ionic liquid to form an ordered adsorption layer on the surface of the mesoporous silica, further inhibiting the free diffusion of the ionic liquid; at the same time, the polar C-F bonds in the PVDF molecular chain have a strong dipole moment, which can generate dipole-ion interactions with the cations and anions in the ionic liquid. Therefore, the mesoporous silica and the PVDF polymer matrix together form a synergistic confinement effect, so that the ionic liquid is doubly fixed by the pore confinement and polymer chain segment interactions.

[0025] Ion conduction in ionic liquids is essentially the directional migration of anions and cations under the influence of an electric field or concentration gradient. Mesoporous silica, with its relatively uniform pore size and large pore volume, provides a stable storage and confinement space for ionic liquids, forming relatively regular ion migration regions and reducing disordered diffusion and local retention of ionic liquids in the polymer matrix. When pressure is applied, the pore structure, interfacial spacing, and local ion concentration within the composite material change, causing rapid alterations in ion migration paths and charge distribution. After pressure is released, the polymer matrix gradually recovers, and the rigid pore structure of mesoporous silica facilitates the redistribution of ionic liquids and their return to their initial state. This reduces signal hysteresis caused by the asynchronous ion migration and structural recovery, resulting in a sensor with low hysteresis characteristics.

[0026] The migration and aggregation of ionic liquids can cause initial resistance and capacitance values ​​of sensors to drift under zero pressure, i.e., baseline drift. However, in the aforementioned multi-component composite functional material system formed from mesoporous silica, the unique structure of mesoporous silica allows the distribution of ionic liquids within the material to reach a dynamic equilibrium, maintaining stability even during long-term use. Furthermore, the restoration of the polymer network further ensures the stability of the material's macroscopic morphology, ultimately stabilizing the signal baseline. In addition, at the electrode-sensing layer interface, the ionic liquid can form an electric double-layer capacitor; the ordered structure of mesoporous silica makes the ion distribution at this interface more uniform and stable, making changes in the area and thickness of the electric double layer caused by pressure variations highly reversible. This avoids the interfacial capacitance hysteresis phenomenon caused by disordered ion distribution in pure ion gels.

[0027] In one possible implementation, the aforementioned polymeric material includes at least one of PVDF, TPU, PVDF-HFP, PU, ​​and PAN; the aforementioned room-temperature ionic liquid includes at least one of [EMIM][TFSI], [EMIM][TFA], [R-Py][X], and [NR4][X].

[0028] Optionally, when the above-mentioned polymer is formed by compounding TPU and PVDF, the mass ratio of TPU to PVDF can be 7:3-6:4. TPU is mainly used to provide flexibility and elasticity, while PVDF, as a semi-crystalline polymer, has crystalline regions that act as physical reinforcing areas dispersed in the polymer matrix, thereby improving the modulus and structural stability of the composite material. Simultaneously, the polar C-F bonds in the PVDF molecular chain can generate ion-dipole interactions with the ionic liquid, helping to restrict the free migration of the ionic liquid and improve its stability within the polymer matrix. Optionally, if the polymer is a blend of PU and PAN, the mass ratio can be 8:2-7:3, where PU provides an elastic framework and rapid recovery capability, and the nitrile groups of PAN form strong coordination with the ionic liquid cations, promoting ion dissociation and increasing local ion concentration. If it is a blend of PVDF-HFP and PAN, the mass ratio can be 6:4-5:5, where PVDF-HFP provides an electrochemical window and dielectric response, and PAN provides ion coordination and mechanical strength. If it is a blend of TPU and PU, the mass ratio can be 5:5-4:6, where the thermoplasticity of TPU makes it easy to process and recycle, and the cross-linked structure of PU provides higher elastic recovery and creep resistance. If TPU, PVDF-HFP, PU and PAN are compounded, the mass ratio of the compound can be 4:2:3:1. Among them, the soft segment of TPU / PU dominates the deformation response, the crystalline region of PVDF-HFP disperses stress, and the nitrile group of PAN anchors ions. The polar groups of the four polymers form multiple hydrogen bonds and coordination networks with ionic liquid and mesoporous silica, which can further improve ion retention ability and interfacial stability.

[0029] Optionally, when the above room-temperature ionic liquid is composed of [EMIM][TFSI] and [EMIM][TFA], the blending mass ratio can be 7:3-8:2. After blending, the anion size distribution becomes more diverse, and the synergistic effect of ion migration further optimizes the overall transport efficiency. If it is composed of [EMIM][TFSI] and [BPy][TFSI], the blending mass ratio can be 6:4-5:5, where [BPy]... + The introduction of [EMIM][TFSI] modulates the interfacial polarity between the ionic liquid and PVDF-HFP (C-F affinity) and PAN (nitrile repulsion / attraction), resulting in a more uniform ion distribution and reducing local enrichment. Furthermore, the conjugated structure of the pyridine ring enhances the π-π stacking interaction with mesoporous silica, promoting ion filling of the mesoporous silica channels. If [EMIM][TFSI] and [N] are used... 1111 [TFSI] is compounded, and the compounded mass ratio can be 8:2-7:3, where [N 1111 ] + (Tetramethylammonium) may have a smaller volume than [EMIM] + Generally, it has a spherical symmetrical structure and does not easily form strong coordination with polymers; the introduction of quaternary ammonium cations can significantly widen the liquid range of ionic liquids, lower the glass transition temperature, and enable the material to maintain high ionic conductivity at low temperatures; at the same time, the coexistence of large and small cations makes the ion filling in the mesoporous silica channels more dense, enhancing the confinement effect. If [EMIM][TFSI], [EMIM][TFA], [BPy][TFSI] and [N 1111[TFSI] Quaternary blends can have a mass ratio of 5:2:2:1. The quaternary blend system can improve the conductivity, viscosity, electrochemical window, low-temperature fluidity, and interfacial compatibility of the system. Multiple ion pairs compete to fill the mesoporous silica channels, forming a gradient distribution. The ion transport paths are diversified, and the pressure response sensitivity remains linear over a wide range. However, due to the high complexity of the system, if this blend system is used, it is necessary to verify whether anion exchange leads to performance drift in practical applications.

[0030] It should be understood that the above-mentioned PVDF (polyvinylidene fluoride), TPU (thermoplastic polyurethane), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene copolymer), PU (polyurethane) and PAN (polyacrylonitrile) are all polymers containing polar groups, can all be used as electrolyte matrices, and all have film-forming properties.

[0031] The above [EMIM][TFSI] refers to 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, [EMIM][TFA] refers to 1-ethyl-3-methylimidazolium trifluoroacetate, [R-Py][X] refers to ionic liquids containing pyridine groups, such as [BPy][BF4] (butylpyridine tetrafluoroborate), and [NR4][X] refers to ionic liquids containing quaternary ammonium groups, such as [N 1111 [TFSI] (Tetramethylammonium bis(trifluoromethanesulfonyl)imide).

[0032] In the technical solution of this invention, in addition to the specific types of polymers and room-temperature ionic liquids disclosed above, the polymers can also be selected in a multidimensional way, such as polyethers (PEO), polypropylene oxide (PPO), polyacrylates (PMMA), polyethyl methacrylate (PEMA), polysiloxanes, or other fluorinated polymers, natural polymers and derivatives (such as polyvinylidene fluoride (PVDF), cellulose, etc.). For the room-temperature ionic liquids, imidazoles (such as 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imine salt ([HMIM][TFSI]), pyrrolidines, morpholine, piperidine, etc., can also be selected.

[0033] It should be noted that in the above-mentioned multi-component composite functional material system formed by mesoporous silica, when the polymer includes one of PVDF, TPU, PVDF-HFP, PU, ​​and PAN, TPU and PU can provide a hydrogen bond network of urethane bonds, endowing the material with high elasticity and self-healing potential; PVDF-HFP can introduce a semi-crystalline structure and strongly polar C-F bonds, enhancing electrochemical stability and dielectric response; and the nitrile groups of PAN can interact strongly with the ionic liquid cations, promoting ion dissociation. When the room temperature ionic liquid includes one of [EMIM][TFSI], [EMIM][TFA], [R-Py][X], and [NR4][X], [EMIM][TFSI] can provide high conductivity and a wide electrochemical window; [EMIM][TFA] can reduce the viscosity of the system and improve low-temperature fluidity; [R-Py][X] can adjust the interfacial polarity with the polymer through the rigid planar structure of the pyridine ring; and the large-volume cations of [NR4][X] can disrupt the ordered stacking of the ionic liquid and inhibit crystallization tendency. When multiple cations coexist, ion exchange and competitive coordination occur, forming a complex ion distribution within the mesoporous silica channels. This distribution can be selectively regulated by the polar groups on the pore walls of the mesoporous silica.

[0034] Furthermore, when the aforementioned polymers are compounded into multiple components, such as when a polymer matrix is ​​formed by compounding PAN, PVDF-HFP, TPU, and / or PU, the different polymer components can exert synergistic effects. The nitrile groups in PAN and the polar C-F bonds in PVDF-HFP can interact with ionic liquids, thereby regulating the distribution and migration of ionic liquids in different polymer regions. Mesoporous silica has a high specific surface area and abundant mesoporous channels, which can load and confine ionic liquids; the silanol groups on its pore wall surface can also form hydrogen bonds or interfacial interactions with ionic liquids, thereby reducing the free migration of ionic liquids. Optionally, the surface of mesoporous silica can be functionalized to improve its interfacial compatibility with PAN, PVDF-HFP, TPU, and / or PU, thereby achieving regulation of ion distribution and transport behavior. Under low pressure, the flexible segments of TPU and / or PU preferentially deform, altering the pore structure, interfacial spacing, and local ion concentration within the composite material, thus generating an initial electrical signal. As pressure increases, the crystalline regions of PVDF-HFP, the rigid segments of PAN, and mesoporous silica gradually contribute to stress bearing. Mesoporous silica disperses stress and limits excessive local deformation, thereby improving the composite material's compressive strength and structural stability. Upon pressure unloading, the elastic recovery of the flexible segments of TPU and / or PU provides the primary restoring force, the crystalline regions of PVDF-HFP restrict irreversible slippage of polymer segments, and the mesoporous silica reduces permanent deformation and the continued migration of ionic liquids through rigid support, interfacial constraints, and pore confinement. Therefore, the synergistic effect between different components helps the sensor maintain a stable response over a wide pressure range and improves its linearity, hysteresis characteristics, and cycling stability.

[0035] In multi-component compound systems, the synergistic effect of different components can broaden the range of applicable conditions for materials. For example, PVDF-HFP combined with [TFSI] - Ionic liquids exhibit good electrochemical stability, which helps to broaden the electrochemical stability window of the system. The combination of TPU and / or PU with low-viscosity ionic liquids can improve the mobility of polymer chain segments under low-temperature conditions, allowing the material to maintain a certain degree of flexibility and elasticity at lower temperatures, and reducing embrittlement and cracking caused by glass transition.

[0036] In addition, by selecting ionic liquids with strong hydrophobicity, such as those containing [TFSI] -Ionic liquids or long-chain quaternary ammonium salt ionic liquids, used in combination with fluoropolymers such as PVDF-HFP, can reduce the absorption of environmental moisture by the system and improve its moisture resistance. Mesoporous silica has high thermal and chemical stability, and its rigid inorganic framework can improve the structural stability of composite materials. At the same time, the interfacial interaction between the mesoporous channels and pore wall surfaces can load and confine the ionic liquid, reducing the migration, leakage, and local accumulation of the ionic liquid during long-term use, thereby improving the environmental adaptability and long-term reliability of sensitive elements. To achieve the above objectives, the present invention also provides a method for preparing a sensitive element comprising a composite functional material, for preparing the aforementioned sensitive element, the method comprising: S10. An ionic gel system is prepared by adding a room-temperature ionic liquid to a solution of a polymer. S20. Mesoporous silica powder phase is added to the ion gel system of S10 to prepare a multi-component composite functional material system formed by mesoporous silica; S30. Based on the sensitive element fabrication process, the multi-component composite functional material system formed from mesoporous silica in S20 is used to prepare the aforementioned sensitive element.

[0037] It should be noted that in the above preparation method, after adding a room-temperature ionic liquid to the polymer solution, as the solvent evaporates or the polymer concentration increases, the polymer chains gradually entangle and cross-link, forming an ionic gel system with a three-dimensional network structure. At this point, the ionic liquid is distributed within this network structure, possessing ionic conductivity. This structure appears as a solid phase, filled with mobile ions, making it a hybrid material with a solid appearance and a liquid core. In this ionic gel system, the ionic liquid serves as both a dispersion medium and a highly efficient plasticizer. After combining with the polymer, the polymer network provides elastic recovery and shape retention, while the ionic liquid imparts low modulus and high deformation capacity, resulting in a material with high tensile strength. Furthermore, the room-temperature ionic liquid has a wide electrochemical window, allowing the gel system to withstand higher operating voltages; and it can form a stable double-layer structure at the electrode interface, which is beneficial for the long-term cycling stability of the sensor.

[0038] Adding mesoporous silica powder to the aforementioned ionogel system, under appropriate dosage and dispersion conditions, typically does not disrupt the overall continuity of the polymer network. Instead, it embeds itself within the polymer matrix as a dispersed filler or physical reinforcing node. Mesoporous silica possesses abundant pore structures, providing nanoscale confinement spaces for ionic liquids. Once the ionic liquid enters the mesoporous channels, its ion arrangement, local concentration, and movement are constrained by the pore walls and pore size, forming a confined state different from that of bulk ionic liquids. This confinement effect can regulate the local coordination environment, distribution state, and migration behavior of ions, and under suitable pore size, filling amount, and interfacial interaction conditions, it helps to form a relatively stable ion transport region. The pore walls of mesoporous silica typically contain silanol groups and siloxane bonds, which can generate hydrogen bonds, electrostatic interactions, or other interfacial interactions with ionic liquids, thereby increasing the affinity between mesoporous silica and ionic liquids and reducing disordered diffusion and local aggregation of ionic liquids. Optionally, the surface of mesoporous silica can be functionalized by introducing amino, nitrile, or other polar groups to further regulate its interfacial interactions with ionic liquids. Meanwhile, the high specific surface area of ​​mesoporous silica can increase the contact area between the ionic liquid and the solid pore wall. The charge enrichment layer and interfacial polarization effect formed at the interface can change the dissociation and migration state of ions, thereby helping to improve the stability of ion conduction.

[0039] In multi-component composite functional material systems formed from mesoporous silica, mesoporous silica acts as a rigid nanoframework dispersed in a flexible polymer-ionic liquid matrix. It serves as a physical crosslinking point and stress transfer center. When the material is subjected to tension or compression, the mesoporous silica particles can withstand some of the stress, preventing excessive slippage and irreversible deformation of the polymer chains. Furthermore, mesoporous silica and the polymer matrix can form organic-organic interfaces through hydrogen bonding, π-π stacking, or coordination interactions. The interfacial compatibility may be superior to that of inorganic fillers, resulting in higher stress transfer efficiency and reducing the likelihood of stress concentration and cracking at the interface. Ultimately, the material maintains high flexibility while improving both modulus and strength, and may exhibit better elastic recovery.

[0040] When fabricating a multi-component composite functional material system formed from mesoporous silica into a sensitive element, different fabrication processes can be adopted depending on the characteristics of the target element. For example, if high sensitivity and fast response are desired, electrospinning, template methods, and 3D printing of microstructures can be used; if large area and low cost are required, solution casting and hot pressing can be used; if complex shapes and customized elements are needed, 3D printing and photopolymerization can be used; if micropatterning and arraying of elements are required, photopolymerization and template methods can be used; if gradient and multi-layered structures are required, layer-by-layer self-assembly and multi-step casting processes can be used. In practical applications, multiple methods can also be used in combination to meet various requirements for element characteristics. For example, the substrate can be prepared by electrospinning first, followed by 3D printing of microstructure layers to achieve synergistic optimization of performance.

[0041] In one possible implementation, the method for preparing an ionic gel system by adding a room-temperature ionic liquid to a solution of a polymer includes: The solid phase of the above-mentioned polymer is dissolved in a solvent and magnetically stirred until homogeneous to obtain a polymer-based solution; The room-temperature ionic liquid was added to the polymer-based solution and stirred until homogeneous to obtain an ionic gel system.

[0042] In one possible implementation, the mass ratio of the polymer, room temperature ionic liquid, and solvent in the ionogel system is 1:1:4 to 1:1.5:5.

[0043] Optionally, the solvent mentioned above can be DMF, or it can be selected according to actual needs.

[0044] It should be noted that polymers such as PVDF, TPU, PVDF-HFP, PU, ​​and PAN typically have molecular chains in a coiled or entangled state. If these are directly added to ionic liquids, the polymers are difficult to fully extend and dissolve. Therefore, in the preparation of the ionic gel system described above, the polymer is first dissolved in a solvent. The solvent has low viscosity and high permeability, allowing it to quickly penetrate the polymer interior, disrupting interchain interactions and enabling the polymer chains to fully extend and disperse uniformly. Then, the ionic liquid is added. The ionic liquid can rapidly diffuse in the fully dissolved polymer solution, mixing uniformly with the polymer chains to ultimately form a molecularly homogeneous composite system.

[0045] It should be noted that in the above-mentioned ionogel system, the mass ratio of polymer to room-temperature ionic liquid is in the range of 1:1 to 1:1.5. This range can achieve a balance between mechanical properties and ionic conductivity. When the polymer and ionic liquid are in equal or nearly equal amounts, the polymer segments can form a continuous three-dimensional entangled network, providing sufficient mechanical strength and shape stability for the system. At the same time, the content of ionic liquid is sufficient to form interconnected ion transport channels in the polymer network, ensuring high ionic conductivity. If the polymer ratio is too high, for example, greater than 1:1, the network will be too dense, the ionic liquid will be excessively bound, and the transport path will be broken. If the ionic liquid ratio is too high, for example, greater than 1:1.5, the network will be excessively swollen, and the mechanical strength will decrease sharply. In addition, the mass ratio of solvent can be 4-5 times. This ratio allows the polymer to dissolve completely, the ionic liquid to be uniformly dispersed, and provides sufficient fluid space for the subsequent addition of fillers such as mesoporous silica.

[0046] In one possible implementation, the method for preparing a multi-component composite functional material system by adding mesoporous silica powder phase to an ion gel system includes: Mesoporous silica powder was added to an ion gel system and stirred until homogeneous under ultrasonic conditions to obtain a multi-component composite functional material system formed by mesoporous silica.

[0047] In one possible implementation, in the step of adding the mesoporous silica powder phase to the ionogel system, the amount of the mesoporous silica powder phase added is 1.6-2.5% of the mass of the ionogel system.

[0048] It should be noted that mesoporous silica, as a nanoscale crystalline material, has a high specific surface area and surface energy, making it prone to agglomeration in viscous polymer-ionic liquid systems. Directly mixing the polymer, ionic liquid, and mesoporous silica can lead to particle separation due to polymer chain entanglement and the high viscosity of the ionic liquid, resulting in difficulty in achieving uniform dispersion. In the aforementioned solution, mesoporous silica powder is added to the ionogel system and uniformly stirred under ultrasonic conditions. The cavitation effect and microturbulence generated by ultrasonic stirring allow the ionic liquid to penetrate deep into the mesoporous silica pores, displacing the gas and solvent within the pores and achieving complete wetting and filling. Furthermore, it promotes in-situ interfacial activation between the polar groups on the mesoporous silica surface and the polymer chains and ionic liquid molecules. This activation may enhance the formation of hydrogen bonds, coordination, or dipole interactions, creating a chemical-physical dual coupling between the mesoporous silica and the matrix, ultimately improving the interfacial bonding strength and enhancing the overall mechanical properties of the material.

[0049] Furthermore, when the amount of mesoporous silica powder added is 1.6-2.5% of the mass of the ionogel system, the distribution density of mesoporous silica nanoparticles in the polymer-ionic liquid matrix may reach a critical point, and the interparticle spacing shrinks to the nanoscale, enabling the formation of a localized percolation network. This network is not a continuous rigid framework, but exists in the form of island bridges, in which mesoporous silica particles act as nodes and are interconnected through polymer segments or ionic liquid layers, forming partial pathways that penetrate the material. This structure can introduce ordered ion transport channels and stress transmission paths while maintaining the flexibility of the matrix. If the content deviates from this range, for example, if the mesoporous silica content is <1.6%, it may lead to an increase in the interparticle spacing, making it difficult to form an effective permeation network. The mesoporous silica will be in an isolated and dispersed state in the matrix, and its ordered channels may be surrounded by polymer chain segments, making it difficult for ionic liquids to effectively enter the channels. If the content is >3.5%, it may lead to a further reduction in the interparticle spacing, and physical contact and agglomeration will begin to occur. The high surface energy of nanoparticles makes them tend to aggregate to reduce the surface energy, forming micron-sized or even larger agglomerates. These agglomerates may become stress concentration points, triggering crack initiation and propagation during tension or compression, resulting in a decrease in the elongation at break and an increase in brittleness of the material.

[0050] In one possible implementation, when the sensing element is fabricated using a solution casting method, the method described above for fabricating a multi-component composite functional material system formed from mesoporous silica into a sensing element based on the sensing element fabrication process includes: A multi-component composite functional material system formed from mesoporous silica is poured into a mold, coated with a scraper to a uniform thickness, and then subjected to preliminary drying and heat curing to obtain the sensitive element.

[0051] Optionally, the mold used in the above solution casting method is not limited and can be selected according to existing processes.

[0052] In one possible implementation, in the steps of preliminary drying and heat curing, the temperature of preliminary drying is 30-50°C and the time is 30-45 min; the temperature of heat curing is 75-90°C and the time is 5.5-6.5 h.

[0053] It should be noted that when using solution casting to prepare sensitive elements, after the material system is uniformly coated, the solvent content is high, and the system is in a viscous, fluid state. If directly placed in a high-temperature environment, the surface solvent will evaporate rapidly, forming a dense surface skin. This skin will hinder the diffusion of the internal solvent outward, causing the solvent to form bubbles, pores, or delamination defects inside the film. Therefore, in the above preparation method, preliminary drying is first performed at a low temperature of 30-50°C, where the solvent initially evaporates, keeping the solvent concentration gradient between the material surface and interior gradual. Simultaneously, as the solvent slowly decreases, the polymer segments begin to approach each other, initially forming a physical entanglement network. The ionic liquid is gradually embedded in the network voids, and the position of the mesoporous silica particles is also fixed. After 30-45 minutes, the film changes from a fluid state to a semi-solid state.

[0054] After initial drying, solvent molecules remain in the film, tightly bound to the polymer chains or ionic liquids through hydrogen bonds and coordination. If these residual solvents are not fully removed, they will slowly seep out during sensor operation, leading to changes in ionic liquid distribution, electrode interface contamination, and signal baseline drift. Therefore, in the above scheme, after initial drying, heat curing is performed. Within a temperature range of 75-90℃, the residual solvents can acquire sufficient diffusion kinetic energy, gradually desorbing from the free volume of the polymer and the mesoporous silica channels and migrating to the surface for volatilization. A holding time of 5.5-6.5 hours ensures that the solvents are fully overflowed and removed. During this stage, heat treatment gives the polymer chains a certain degree of mobility, which is beneficial for further chain rearrangement, residual solvent removal, and crystal structure adjustment, thereby improving the uniformity and stability of the internal structure of the sensing element. For the PVDF-HFP polymer matrix, heat treatment can promote chain rearrangement and, under suitable conditions, make the local structure more ordered. Meanwhile, the silanol groups and siloxane bonds on the surface of the mesoporous silica pore walls can form hydrogen bonds, dipole-ion interactions, electrostatic interactions, or other interfacial interactions with ionic liquids and polymer matrices, thereby forming a synergistic interfacial system composed of the polymer matrix, mesoporous silica, and ionic liquids. Furthermore, heat treatment helps the ionic liquid to further penetrate and stably distribute within the pores of the mesoporous silica, enhancing pore confinement and interfacial adsorption, thus reducing migration, leakage, and localized aggregation of the ionic liquid during long-term use, and improving the structural stability and reliability of the sensitive element.

[0055] To achieve the above objectives, the present invention also provides a low-hysteresis ion gel pressure sensor, which includes the aforementioned sensitive element.

[0056] It should be understood that in the low-hysteresis ion gel pressure sensor disclosed in this invention, the core position of the sensitive element in the sensor is the functional sensitive layer between the electrodes. It is both an ion conductor (providing an electrical signal path) and a mechanical response layer (converting pressure into changes in electrical signals). Its specific structural position depends on the type of sensor. For example, it can be in the middle of the electrodes, where the thickness changes under pressure, causing changes in resistance and capacitance; it can also be a microstructure interface type, which can increase the rate of change of contact area and significantly improve the sensitivity of the sensor; or it can be an ion gel-dielectric layer composite type, which causes changes in the capacitance of the electric double layer (EDL) when the sensor senses pressure, resulting in a faster response; or it can be an ion gel coating type, which can be applied to large-area, low-cost applications; or it can be a self-supporting all-gel type, which can serve as both a sensitive layer and a structural support layer, and can conform to any curved surface.

[0057] Optionally, the above-mentioned method for embedding the sensitive element into the sensor can be as follows: according to actual needs, the thin film of the obtained sensitive element is cut to the target size and shape, then placed between Ag-TPU electrodes formed by screen printing, ensuring good contact between the film and the electrodes, and finally encapsulated to obtain a pressure sensor.

[0058] It should be understood that in the structure of a pressure sensor, the sensitive element is generally located between the upper and lower electrodes, forming a sandwich-like sandwich structure. When external pressure is applied to the sensor surface, the pressure is first transmitted to the upper electrode, which then transmits the mechanical force to the sensitive element in the middle. The sensitive element undergoes deformation or changes in its internal structure, resulting in changes in its electrical characteristics. This change is extracted through the upper and lower electrodes and is ultimately captured by the detection circuit.

[0059] Optionally, in a single-layer thin-film pressure sensor, the sensing element can be laid flat on a substrate, with a flexible electrode layer covering both the top and bottom; pressure applied to the film surface causes the entire sensing layer to respond synchronously. In a microstructure-type pressure sensor, the sensing element can be fabricated into specific micromorphologies, such as micro-pyramid arrays or micro-pillar arrays. These microstructures are located at the contact interface of the electrodes; in this case, the top of the microstructure of the sensing element becomes a pressure concentration point, where even a small pressure can cause significant local deformation, thereby amplifying the signal response. In a capacitive pressure sensor, the sensing element can also act as a dielectric layer, located between two parallel electrode plates; pressure changes the thickness of the sensing element, thus changing the capacitance value.

[0060] It should be noted that when the pressure sensor includes the aforementioned sensitive elements, the ion transport response in the ion gel is extremely fast. The migration and rearrangement of ions under electric and pressure fields are fast kinetic processes, potentially reaching the millisecond level. Furthermore, the pores of mesoporous silica can further shorten the ion transport path, reducing ion retention in complex networks, thus giving the sensor low hysteresis, fast response, and rapid recovery characteristics. Secondly, by limiting the ratio of polymer to ion solution, the modulus of the ion gel can undergo significant deformation under small pressures. The introduction of mesoporous silica provides additional fast ion transport channels, and the density of these channels changes significantly under pressure, increasing the rate of change of resistance or capacitance. Simultaneously, the intrinsic flexibility of the ion gel allows the sensor to maintain a linear response over a wide pressure range, thus giving the sensor high sensitivity and a wide linear range. In addition, the multi-component composite functional material system formed from mesoporous silica can also endow the pressure sensor with properties such as flexibility, stretchability, wide temperature adaptability, anti-interference, and high stability.

[0061] Example 1 A sensing element comprising a composite functional material is prepared from a multi-component composite functional material system formed from mesoporous silica; in the multi-component composite functional material system formed from mesoporous silica, the polymer is PVDF and the room temperature ionic liquid is [EMIM][TFSI]. The method for preparing this sensitive element is as follows: S10. Take PVDF powder, [EMIM], [TFSI] and DMF in a mass ratio of 1:1:4 respectively; dissolve PVDF powder in DMF and stir magnetically until homogeneous; then add [EMIM] and [TFSI] and continue stirring until homogeneous, so that the ionic liquid is fully dispersed and penetrates into the polymer chain segments, thereby forming a compliant and homogeneous ionic gel system. S20. Weigh out 1.6% of the mass of the ion gel system (S10), add MCM-41 type mesoporous silica powder phase to the ion gel system, and stir until uniform under ultrasonic conditions to obtain a multi-component composite functional material system formed by MCM-41 type mesoporous silica. S30. Pour the multi-component composite functional material system formed by MCM-41 type mesoporous silica from S20 into a mold, scrape it with a scraper to a uniform thickness, pre-dry it at 30℃ for 45 min, and then heat it at 75℃ for 6.5 h to obtain the thin film morphology of the sensitive element.

[0062] The thin film morphology of the sensing elements obtained from S10 to S30 was measured under a microscope, and the results are as follows: Figure 1 As shown.

[0063] like Figure 1The dominant dark gray continuous region represents the substrate phase, with a smooth and continuous surface. Light-colored and white particles and clusters distributed on the substrate phase surface constitute the dispersed phase. Compared to a 100 μm scale, the size of these dispersed phases is approximately in the nanometer to micrometer range. The relatively uniform distribution of the dispersed phase indicates good dispersion of the filler within the matrix. Further analysis reveals that the discretely distributed dispersed phase in the figure may represent protrusions of mesoporous silica nanoparticles on the substrate phase surface. Furthermore, in areas of particle aggregation, micro-wrinkles and collapses may form due to localized stress or solvent evaporation. These protrusions, wrinkles, and collapses collectively constitute the rough structure of the film surface, i.e., the aforementioned rough surface structure. In the field of pressure sensors, this rough surface structure can increase the specific surface area of ​​the film, amplifying changes in capacitance, resistance, or piezoelectric charge accumulation at the interface, thereby improving sensing sensitivity. Simultaneously, the rough surface structure also facilitates the formation of more microscopic contact points between the film and the electrodes and the measured medium, improving interfacial coupling efficiency. Secondly, the densely packed particle dispersion in some areas of the figure may form interstitial channels between the particles. Based on the possibility that the ionic liquid may be anchored inside the mesoporous silica channels and enriched in the amorphous region of PVDF, and based on the fact that mesoporous silica can provide rigid channels, the three factors work together to form a multidimensional interpenetrating network structure with multiple interwoven structures.

[0064] According to actual needs, the thin film of the sensitive element in the embodiment is cut to the target size and shape, and then placed between Ag-TPU electrodes formed by screen printing, ensuring good contact between the film and the electrodes, and then encapsulated to obtain a low-hysteresis ion gel pressure sensor. The performance of this low-hysteresis ion gel pressure sensor is measured, and the test data are as follows: Figure 2 As shown.

[0065] like Figure 2 The pressure-capacitance curves of the sensor are shown in the figure. As can be seen, the multiple cyclic curves from various tests highly overlap, indicating that the sensor exhibits good reversibility and recoverability during the pressurization-depressurization process, with extremely low hysteresis. Furthermore, the capacitance continuously increases with increasing pressure, with the rate of increase decreasing gradually, forming an upward-convex curve. In the low-pressure range of 0–200 kPa, the curve slope is the steepest, and the capacitance rapidly jumps from the baseline to approximately 1.2 × 10⁻⁶ kPa. -8 F indicates that the sensor has the highest sensitivity in the low-pressure range; entering the medium-pressure range of 200–400 kPa, the slope slows down significantly, and the capacitance increases to approximately 1.75 × 10⁻⁶. -8 F; When the pressure exceeds 400 kPa, the curve becomes flatter.

[0066] Analysis of the structure of the thin film suggests that the mechanism behind this phenomenon may be as follows: Under low pressure, the rough structure on the film surface undergoes microscopic deformation, rapidly expanding the contact area between the rough peaks and the opposite electrode, thus significantly increasing the effective capacitor plate area. Simultaneously, the submicron-level interconnected channels formed by interparticle gaps in the film are compressed, and the [EMIM][TFSI] ionic liquid enriched within the channels redistributes, with ions migrating to the electrode interface and forming a denser double-layer structure at the interface. Furthermore, the PVDF matrix undergoes elastic deformation under low pressure, reducing the film thickness. According to the parallel plate capacitance principle, geometric compression itself can directly increase the capacitance value. During this stage, the large pores and gaps in the multi-level channels provide ample compressible space, thus enabling the sensor to exhibit an extremely sensitive low-pressure response capability. As the pressure increases further, the external force begins to act on the mesoporous framework of the mesoporous silica particles themselves, and the capacitance growth rate slows down. At the same time, the PVDF matrix may undergo partial crystal region orientation or α→β crystal phase transformation within this pressure range, resulting in an increase in dielectric constant. When the pressure exceeds 400 kPa, the film structure is further compressed, and the mesoporous silica particles move closer to each other or form local dense packing, slowing down the capacitance increase rate. This indicates that the film has self-protection characteristics within a wide pressure range and is not prone to irreversible structural damage due to overload.

[0067] Example 2 A sensing element comprising a composite functional material is prepared from a multi-component composite functional material system formed from mesoporous silica; in the multi-component composite functional material system formed from mesoporous silica, the polymer is composed of PU and PVDF, and the room temperature ionic liquid is composed of [EMIM][TFSI] and [EMIM][TFA]. The method for preparing this sensitive element is as follows: S10. Take the powder phase of the polymer, the room temperature ionic liquid and DMF in a mass ratio of 1:1.5:5 respectively; wherein the polymer is composed of PU and PNA in a mass ratio of 1:1, and the room temperature ionic liquid is composed of [EMIM][TFSI] and [EMIM][TFA] in a mass ratio of 7:3. Polymer particles are dissolved in DMF and stirred magnetically until homogeneous; then room temperature ionic liquid is added and stirred until homogeneous, so that the ionic liquid is fully dispersed and penetrates into the polymer chain segments, thereby forming a compliant and homogeneous ionic gel system. S20. Weigh out 3.5% of the mass of the ion gel system with an addition amount of S10, add the MCM-41 type mesoporous silica powder phase to the ion gel system, and stir until uniform under ultrasonic conditions to obtain a multi-component composite functional material system formed by MCM-41 type mesoporous silica. S30. Pour the multi-component composite functional material system formed by MCM-41 type mesoporous silica of S20 into the mold, scrape it with a scraper to a uniform thickness, pre-dry it at 50℃ for 30 min, and then heat it at 90℃ for 5.5 h to obtain the thin film morphology of the sensitive element.

[0068] The thin film of the sensitive element is cut to the target size and shape according to actual needs, and then placed between Ag-TPU electrodes formed by screen printing, ensuring good contact between the film and the electrodes. It is then encapsulated to obtain a low-hysteresis ion gel pressure sensor. The performance of this low-hysteresis ion gel pressure sensor is measured, and the test data are as follows: Figure 3 As shown.

[0069] like Figure 3 The figure shows the pressure-capacitance curve test graph of the sensor. As the pressure increases, the trend of the curve is similar to... Figure 2 The basic consistency indicates that the technical solution disclosed in this invention has high repeatability, and the thin film morphology and performance of the obtained sensitive element are stable.

[0070] Example 3 A sensing element comprising a composite functional material is fabricated from a multi-component composite functional material system formed from mesoporous silica. In this system, the polymer is composed of TPU and PAN, and the room-temperature ionic liquid is composed of [EMIM][TFSI], [EMIM][TFA], [BPy][TFSI], and [N]. 1111 [TFSI] Composition; The method for preparing this sensitive element is as follows: S10. Take the polymer powder phase, room temperature ionic liquid, and DMF in a mass ratio of 1:1:4; wherein, in the polymer powder phase, the mass ratio of PU to PAN is 8:2; and in the room temperature ionic liquid, [EMIM][TFSI], [EMIM][TFA], [BPy][TFSI], and [N] are present in the ionic liquid. 1111 The mass ratio of [TFSI] is 5:2:2:1; The powdered phase of the polymer was dissolved in DMF and stirred magnetically until homogeneous. Then, a room temperature ionic liquid was added and stirred until homogeneous, so that the ionic liquid was fully dispersed and penetrated into the polymer chain segments, thereby forming a compliant and homogeneous ionic gel system. S20. Weigh out 2.0% of the mass of the ion gel system with an addition amount of S10, add the MCM-41 type mesoporous silica powder phase to the ion gel system, and stir until uniform under ultrasonic conditions to obtain a multi-component composite functional material system formed by MCM-41 type mesoporous silica. S30. Pour the multi-component composite functional material system formed by MCM-41 type mesoporous silica from S20 into a mold, scrape it with a scraper to a uniform thickness, pre-dry it at 40℃ for 35 min, and then heat it at 85℃ for 6.0 h to obtain the thin film morphology of the sensitive element.

[0071] Comparative Example 1 Comparative Example 1 was set up under Example 1. In Comparative Example 1, PVDF was replaced with an equal amount of polybutyl acrylate (PBA), and all other technical features were the same as those in Example 1.

[0072] Comparative Example 2 Comparative Example 2 was set up under Example 2. In Comparative Example 2, an equal amount of multi-walled carbon nanotubes replaced mesoporous silica. All other technical features were the same as in Example 2.

[0073] Comparative Example 3 Comparative Example 3 was set up in Example 2. In Comparative Example 3, an equal amount of composite graphene material formed by dissolving graphene, 1,3,5-benzenetriformaldehyde and 1,4-phenylenediamine in a solvent, or an equal amount of commercially available finished composite graphene material, was used to replace mesoporous silica. All other technical features were the same as in Example 2.

[0074] The thin films of the sensitive elements obtained in Examples 1-2 and Comparative Examples 1-3 were applied to ion gel type pressure sensors, and the hysteresis performance of the obtained sensors was tested. The results are shown in Table 1.

[0075] Table 1

[0076] Analysis of the data in Table 1 shows that the hysteresis of the examples is less than 4%, indicating that the ion migration and mechanical deformation of the obtained ion gel pressure sensor are highly reversible and have excellent performance. In contrast, the hysteresis of Comparative Examples 1-3 is relatively high. In Comparative Example 1, after replacing PVDF with PBA, the mechanical strength and dimensional stability of the film both decrease. This is because PVDF is a semi-crystalline polymer, and its crystalline regions can serve as physical reinforcement areas, which can improve the modulus and load-bearing capacity of the material. PBA, on the other hand, has a lower glass transition temperature and exhibits a relatively soft and elastic state at room temperature. In addition, uncrosslinked or unreinforced PBA lacks stable crystalline reinforcement regions, which may lead to large viscoelastic deformation and creep under pressure, resulting in a reduced material recovery rate and increased permanent deformation, thereby increasing the hysteresis of the sensor and reducing its cycle stability. Meanwhile, the ionic liquid... The state of PVDF may change, and the dense polar C-F bonds in the PVDF molecular chain can generate ion-dipole interactions with ionic liquids. Its crystalline regions can also restrict the macroscopic migration of ionic liquids. Although PBA contains polar ester groups and can also interact with ionic liquids, its chain segments have strong mobility and lack the physical constraints of PVDF crystalline regions. Therefore, replacing PVDF with PBA may increase the migration freedom of ionic liquids, increasing the risk of ionic liquid leakage, surface enrichment, or local phase separation during long-term storage or cyclic pressure, thereby causing signal baseline drift and performance degradation. In addition, the dispersion and reinforcement effects of mesoporous silica may be affected. The silanol groups on the surface of mesoporous silica can form hydrogen bonds with the carbonyl groups in the PBA ester groups, weakening the rigidity reinforcement and stress dispersion effects of mesoporous silica.

[0077] In Comparative Example 2, after replacing mesoporous silica with multi-walled carbon nanotubes (MWCNTs), MWCNTs are electronic conductors, and their sensing mechanism is based on the change in electron permeation network density caused by pressure. Under pressure, the spacing between carbon nanotubes decreases, the probability of electron tunneling increases, and the resistance decreases; upon unloading, the network recovers, and the resistance rises again. Furthermore, MWCNTs form a randomly entangled network with irregular contact points between tubes, resulting in numerous defects and stress concentrations. MWCNTs have a chemically inert surface, and their interaction with polymers and ionic liquids is primarily based on weak van der Waals forces. Mesoporous silica, on the other hand, is an ion conduction promoter; it is not conductive itself but provides a rapid ion migration path by confining ionic liquids through ordered channels. Its sensing mechanism is based on changes in ion channel density and the interfacial double layer. If MWCNTs are used to replace mesoporous silica, the sensing mechanism of the sensitive element will change from ion conduction type to electron conduction type (piezoresistive type). Potential problems include: under pressure, the carbon nanotubes slip contact; upon unloading, the contact points do not completely separate, leading to non-coincidence of the load-unload curves and a hysteresis response to the rapid ion migration compared to ion conduction. The random network of MWCNTs undergoes irreversible reconstruction during cyclic deformation; carbon nanotubes gradually rearrange, aggregate, or break, causing the initial resistance value under zero pressure to continuously drift; the surface of MWCNTs is hydrophobic and chemically inert, resulting in weak interaction with ionic liquids; ionic liquids are difficult to form an ordered adsorption layer on the surface of MWCNTs, and tend to self-polymerize or combine with polar groups of polymers, which leads to uneven distribution of ionic liquids and an increased risk of leakage; the electronic conductivity of MWCNTs makes them prone to Faraday side reactions in electrochemical environments; if the sensor operating potential is high, the surface of MWCNTs may catalyze the decomposition of the electrolyte or self-oxidize, leading to irreversible performance degradation.

[0078] In Comparative Example 3, after replacing mesoporous silica with composite graphene, graphene, being a zero-bandgap semiconductor with extremely high electronic conductivity, demonstrated superior performance. Mesoporous silica, being an electrically insulating material, typically does not directly participate in electron transport during sensor operation. Instead, it primarily loads and confines the ionic liquid through mesoporous channels, and regulates ion distribution and migration behavior through interfacial interactions between the silanol groups on the pore wall surface and the ionic liquid, thus contributing to the formation of a stable ion transport region. Replacing mesoporous silica with composite graphene introduces an electron percolation network within the material, transforming the sensing element from a purely ion-conductive type to an ion-electron hybrid conductive type. This leads to a more complex sensing mechanism, where pressure-induced resistance changes simultaneously involve changes in ion channels and electron contacts, making signal analysis difficult. Baseline drift intensifies, and the breakage and reconstruction of the electron network exhibit relaxation effects, resulting in unstable zero-voltage resistance values. Electrochemical side reactions also occur; under electric field or potential scanning, the graphene surface may catalyze the decomposition of the ionic liquid, reducing the electrochemical window. Graphene has a chemically inert surface, mainly composed of hydrophobic sp² carbon networks. Its interactions with polymers and ionic liquids are dominated by weak van der Waals forces, which can lead to a decrease in interfacial bonding strength. This may result in reduced stress transfer efficiency, and interfacial slippage and debonding may easily occur under pressure, weakening the anchoring ability of ionic liquids.

[0079] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A sensitive element comprising a composite functional material, characterized in that, The sensing element comprises a multi-component composite functional material system formed from mesoporous silica; the multi-component composite functional material system formed from mesoporous silica comprises a polymer and a room-temperature ionic liquid; The sensitive element includes a multi-dimensional interpenetrating channel structure and a rough surface structure.

2. The sensitive element according to claim 1, characterized in that, The polymeric material includes at least one of PVDF, TPU, PVDF-HFP, PU, ​​and PAN; the room-temperature ionic liquid includes at least one of [EMIM][TFSI], [EMIM][TFA], [R-Py][X], and [NR4][X].

3. A method for preparing a sensitive element comprising a composite functional material, used to prepare the sensitive element as described in claim 1 or 2, characterized in that, The preparation method includes: An ionogel system was prepared by adding a room-temperature ionic liquid to a solution of a polymer. Mesoporous silica powder phase was added to the ion gel system to prepare a multi-component composite functional material system formed by mesoporous silica. Based on the sensitive element fabrication process, the multi-component composite functional material system formed from mesoporous silica is used to prepare the sensitive element.

4. The preparation method according to claim 3, characterized in that, The method for preparing an ionic gel system by adding a room-temperature ionic liquid to a solution of a polymer includes: The solid phase of the polymer is dissolved in a solvent and magnetically stirred until homogeneous to obtain a polymer-based solution. The room-temperature ionic liquid was added to the polymer-based solution and stirred until homogeneous to obtain the ionic gel system.

5. The preparation method according to claim 3, characterized in that, The method for preparing a multi-component composite functional material system formed by adding mesoporous silica powder phase to the ion gel system includes: The mesoporous silica powder phase is added to the ion gel system and stirred until homogeneous under ultrasonic conditions to obtain the multi-component composite functional material system formed by mesoporous silica.

6. The preparation method according to claim 3, characterized in that, When the sensing element is fabricated using a solution casting method, the method for fabricating the multi-component composite functional material system formed from mesoporous silica into the sensing element based on the sensing element fabrication process includes: The multi-component composite functional material system formed by mesoporous silica is poured into a mold, coated with a scraper to a uniform thickness, and then subjected to preliminary drying and heat curing to obtain the sensitive element.

7. The preparation method according to claim 4, characterized in that, In the ionogel system, the mass ratio of the polymer, the room-temperature ionic liquid, and the solvent is 1:1:4 to 1:1.5:

5.

8. The preparation method according to claim 5, characterized in that, In the step of adding the mesoporous silica powder phase to the ion gel system, the amount of the mesoporous silica powder phase added is 1.6-3.5% of the mass of the ion gel system.

9. The preparation method according to claim 6, characterized in that, In the steps of preliminary drying and heat curing, the temperature of preliminary drying is 30-50℃ and the time is 30-45 min; the temperature of heat curing is 75-90℃ and the time is 5.5-6.5 h.

10. A low-hysteresis ionogel pressure sensor, characterized in that, The pressure sensor includes the sensitive element as described in claim 1 or 2.